Optimization of coal seam pressure fracturing fluid system in the eastern edge of the Ordos Basin based on IoT sensors - Shuguang Li; Pu Yuan; Huaibin Zhen; Hao Gong (Measurement: Sensors, 2024)
In the eastern edge of the Ordos Basin in China, coalbed methane geological resources are very abundant, and efficient extraction of coalbed methane has become an important demand for energy development strategies and coal safety production. Therefore, this article uses IoT detection technology to optimize the coal seam pressure fracturing fluid system in this area, in order to improve its efficiency and reliability. Through on-site experiments, the relationship between different concentrations of fracturing fluid systems and coal seam permeability was studied. Divide the architecture of the Internet of Things to achieve more efficient information transmission and application. Based on the actual situation of the coal industry, we have constructed a system architecture for the Internet of Things in coal mines. Based on in-depth research on the occurrence characteristics of coalbed methane in the eastern edge of the Ordos Basin and the characteristics of underground fracturing fluid technology in coal mines, we have obtained the viscosity, rheological properties, viscoelasticity of underground fracturing fluid in coal mines, as well as specific requirements for the action of coalbed methane. On this basis, an interaction model between coal seam fracturing proppant and coal reservoir was established, and its mechanical response process was analyzed using numerical simulation methods. Selecting the optimal fracturing fluid ratio can significantly improve the surface wettability and strength of coal samples, while reducing the content of clay minerals and increasing the porosity of coal samples.